Soluble interleukin-1 receptor type 2 plasma levels in Parkinson’s disease: relationship with cardiac autonomic profile before and after peripheral mechanical somatosensory stimulation - Shiffer, Dana; Zamunér, Antonio Roberto; Minonzio, Maura; Bulgheroni, Mara; Porta, Alberto; Leone, Roberto; Bottazzi, Barbara; Garlanda, Cecilia; Colotta, Francesco; Barbic, Franca; Mantovani, Alberto; Furlan, Raffaello (Frontiers in Physiology, 2023)
Introduction: Systemic inflammation promotes neurodegeneration in Parkinson’s disease (PD). Interleukin-1 receptor type 2 (sIL-1R2) plasma levels increase during inflammation. Data on sIL-1R2 in PD patients and its relationship with PD cardiac autonomic profile are limited, given the possible anti-inflammatory effect of vagal activation. Previously, automated mechanical peripheral somatosensory stimulation (AMPSS) enhanced cardiac vagal modulation. Objectives were to 1) evaluate sIL-1R2 plasma concentrations in PD patients and healthy controls and 2) investigate the correlations between sIL-1R2 and cardiac autonomic indices obtained by spectrum analysis of heart rate variability before and after AMPSS. Methods: sIL-1R2 plasma levels were assessed in 48 PD patients and 50 healthy controls. Electrocardiogram and beat-by-beat arterial pressure were recorded at baseline and after 5 AMPSS sessions in 16 PD patients. Results: PD patients had higher sIL-1R2 levels than controls. In the PD subgroup, an inverse correlation between sIL-1R2 and HFnu was found. There was a negative correlation between changes induced by AMPSS on HFnu and sIL-1R2. Discussion: Higher sIL-1R2 levels in PD patients reflect the inflammatory dysregulation associated with the disease. In PD patients, higher sIL-1R2 was associated with reduced cardiovagal tone. Increased cardiovagal modulation following AMPSS was associated with lower sIL-1R2 levels in Parkinson’s disease patients, suggesting inflammatory state improvement.